Pendekatan geomorfologi untuk karakterisasi gerakan massa di daerah aliran sungai Tinalah Kabupaten Kulon Progo Daerah Istimewa Yogyakarta=Geomorphological approach for mass movement characterization in Tinalah Watershed - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The objectives of this research was to identify/ study landforms characteristics, spatial distribution of the mass movements, as well as to evaluate the mass movements characteristics at each of landform unit, that compresing type, feature, and the amount of it. The reasons and the trigger factors of mass movement's phenomenon are slope, rainfall, landuse, litology and geological structure, as well as soil physics characteristic. This study uses the panchromatic black and white aerial photograph, and topographic map to carry out interpretation of landform units and mass movements. Based on that interpretation result, afterwards field check/field observation was done to know the landforms and mass movement characteristics. The results show that there are three landform units, i.e.: landform units of structural, denudational, and fluvial origin. The study area is dominated by landform unit of denudational origin. The denudational processes cover weathering, erosion, and mass movements. Those landform units are characterized by steeply-vertical sloping, strong weathered rock, thick soil, and intensivelyjointed rocks. That landform characteristics and climate condition as well as landuse type have triggered mass movement. There are four mass movements types occurred in the study area, i.e.: fall, slide, slump, and creep.